Effect of the Addition Coconut Shell Powder on Properties of Polyurethane Matrix Composite - Sallal, Hayder Abbas (Nahrain University College of Engineering Journal, 2014)
This work focuses on the preparation of base polyurethane matrix composite materials by (Hand Lay-Up) method, and studying the effect of selected weight fractions (2, 4, 6, 8, and 10) % wt of (coconut shell powder) particles on some properties of the prepared composite. Some mechanical tests were used to evaluate the prepared system (Tensile, Compression, Impact, and Hardness) tests, and a physical test of (Water absorption %), and all tests were accomplished at room temperature. Maximum results of tensile strength, compression strength, impact energy, hardness and water absorption were (31.3 MPa),(53 MPa), ( 0.156 J), (82 Shor (D)), (0.345 %) at using (6% wt, 6% wt , 2% wt , 10% wt ,10% wt ) respectively. Improved properties of the samples reinforcing for the sample as pure, tensile strength increased to double almost and compressive strength by 12% and impact energy up to 4% and hardness by 17% and the percentage of water absorption into doubled.